Experimental Protocol to Test Explicit Motor Learning–Cerebellar Theta Burst Stimulation - Ortelli, Paola; Ferrazzoli, Davide; Maestri, Roberto; Saltuari, Leopold; Kofler, Markus; Alibardi, Alessia; Koch, Giacomo; Spampinato, Danny; Castagna, Anna; Sebastianelli, Luca; Versace, Viviana (Frontiers in Rehabilitation Sciences, 2021)
Implicit and explicit motor learning processes work interactively in everyday life to promote the creation of highly automatized motor behaviours. The cerebellum is crucial for motor sequence learning and adaptation, as it contributes to the error correction and to sensorimotor integration of on-going actions. Non-invasive cerebellar stimulation has been demonstrated to modulate implicit motor learning and adaptation. Our aim is to explore the potential role of cerebellar theta burst stimulation (TBS) in modulating the explicit motor learning and adaptation, in healthy subjects. Cerebellar TBS will be applied immediately before the learning phase of a computerized task based on a modified Serial Reaction Time Task (SRTT) paradigm. Here, we present a study protocol aimed at evaluating the behavioural effects of continuous (cTBS), intermittent (iTBS) or sham TBS on four different conditions: learning, adaptation, delayed recall and re-adaptation of SRTT. We are confident to find modulation of SRTT performance induced by cerebellar TBS, in particular processing acceleration and reduction of error in all conditions induced by cerebellar iTBS, as already known for implicit processes. On the other hand, we expect that cerebellar cTBS could induce opposite effects. Results from this protocol are supposed to advance the knowledge about the role of non-invasive cerebellar modulation in neurorehabilitation, providing clinicians with useful data for further exploiting this technique in different clinical conditions.